DIGITAL INVENTORY OF BIOENERGETIC ASSETS: IMPLEMENTATION OF PRECISION AGRICULTURE TECHNOLOGIES - BILA, Yuliya (Scientific journal «World of Finance», 2025)
Introduction. The digitalization of the economy, the limitation of natural resources, and economic challenges necessitate innovative approaches to the inventory of specific agro-industrial assets. Precision farming has become a vital tool for automated inventory, significantly influencing modern accounting methods. In the context of bioenergy development, where resources depend on the cultivation of energy crops, the accuracy of inventory is critical for effective agro-industrial management. Technologies such as geographic information systems (GIS), GPS navigation, satellite imagery, and drones enable detailed analysis of crop conditions, yield monitoring, and the assessment of available biomass. The use of sensor data and analytical software facilitates the identification of key indicators that form the foundation of objective accounting records. The purpose of the article is to outline the directions for implementing precision farming technologies in the inventory process of bioenergy assets in agricultural enterprises. Results. The study identifies the benefits of digitalized inventory for asset management in agricultural enterprises, including automation of operations, integration with enterprise resource planning (ERP) systems, continuity of execution, predictive analytics, and reductions in labor costs and routine errors. The main technologies applicable for automated inventory of bioenergy assets include satellite imagery, aerial observation by drones, GIS, soil sensors, GPS technologies, Variable Rate Technology (VRT), robotic systems, and electronic agro-activity maps. The study also highlights the outcomes of digital inventory for bioenergy assets, such as quantitative and qualitative assessment of bioenergy assets, efficient land resource utilization, yield forecasting, harvest planning and logistics, biomass loss reduction, and financial valuation of bioenergy assets. Conclusions. Precision farming technologies offer significant opportunities for digital inventory of bioenergy assets, enabling a high level of data accuracy and improved management efficiency. Integrating these technologies with accounting software facilitates automation of accounting processes, reducing human error. This ensures cost reduction, improved data quality, and the creation of environmental sustainability in agricultural enterprises. In the future, these approaches will promote bioenergy as a leading area of renewable energy development.